Respective roles of the DRL receptor and its ligand WNT5 in Drosophila mushroom body development. - Grillenzoni, N.; Flandre, A.; Lasbleiz, C.; Dura, J.M. (Development, 2007)
In recent decades, Drosophila mushroom bodies (MBs) have become a powerful model for elucidating the molecular mechanisms underlying brain development and function. We have previously characterized the derailed (drl; also known as linotte) receptor tyrosine kinase as an essential component of adult MB development. Here we show, using MARCM clones, a non-cell-autonomous requirement for the DRL receptor in MB development. This result is in accordance with the pattern of DRL expression, which occurs throughout development close to, but not inside, MB cells. While DRL expression can be detected within both interhemispheric glial and commissural neuronal cells, rescue of the drl MB defects appears to involve the latter cellular type. The WNT5 protein has been shown to act as a repulsive ligand for the DRL receptor in the embryonic central nervous system. We show here that WNT5 is required intrinsically within MB neurons for proper MB axonal growth and probably interacts with the extrinsic DRL receptor in order to stop axonal growth. We therefore propose that the neuronal requirement for both proteins defines an interacting network acting during MB development.